Simulating sedimentation on the Great Bahama Bank – Sources, sinks and storms. Issue 7 (27th July 2022) - Lopez‐Gamundi, Cecilia; Dobbelaere, Thomas; Hanert, Emmanuel; Harris, Paul M.; Eberli, Gregor; Purkis, Sam J.
Abstract: This study developed a high‐fidelity hydrodynamic simulation of sediment production, transport and deposition for the Great Bahama Bank. This model was run with a time‐step of 15 min for the entirety of 2016, forced by tides, off‐platform circulation and wind. Encompassed in this run are 364 days of fair‐weather conditions and two days when the passage of Category 4 Matthew brought hurricane‐force winds to the platform. This simulation therefore offers an excellent opportunity to contrast the sway of fair‐weather and storm‐weather conditions on sculpting the facies arrangement atop this 100 000 km 2 shallow‐water carbonate platform. The work suggests that fair‐weather conditions are sufficient to deliver the platform's broad‐scale facies patterns. Even the lethargic currents of the platform interior can move mud (<63 μm) over 200 km from its source over the course of one year. Intense focusing of tidal currents between islands and close to the platform margin are ample to move coarse grains (>450 μm), at least locally, as is necessary to produce the vast ooid fairways for which the Great Bahama Bank is famed. Even at the height of Hurricane Matthew, average current speeds in these tidally‐dominated areas do not exceed the speeds simulated for fair‐weather conditions. Hence, the hurricane has negligible effect in these high‐energy areas. The hurricane does not have zero impact, though. For up to 110 km either side of the storm's track, winds exceeding 26 m/s induce currents that winnow mud over longer distances than delivered by fair‐weather conditions. Hence, the storm has a sedimentological signature which, albeit minor, might propagate into the depositional architecture of the platform when scaled over many storms through geological time. This work informs on the role of uniformitarianism versus catastrophism on carbonate sedimentation and casts doubt on geological interpretations of coarse‐grained storm deposits (tempestites) atop shallow‐water platforms.